(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The purpose of this study was to investigate the role of hypoxia-inducible factor HIF-1α in the formation of fetoplacental insufficiency and the development of intrapartum fetal death in preeclampsia. The study included analysis of molecular genetic data in conjunction with Doppler measurements of fetoplacental blood flow. The findings established that HIF-1α hyperexpression is associated with endothelial cell apoptosis, reduced angiogenesis, and critical abnormalities in Doppler indices that precede acute intrapartum fetal hypoxia in preeclampsia.